Exploration of Potential Actinomycetes from CIFOR Forest Origin as Antimicrobial, Antifungus, and Producing Extracellular Xylanase - Sipriyadi Sipriyadi; Yulin Lestari; Aris Tri Wahyudi; Anja Meryandini; Maggy Thenawidjaja Suhartono (Biosaintifika: Journal of Biology & Biology Education, 2016)
This study aimed to isolate and explore the actinomycetes of CIFOR forest origin as an antimicrobial and antifungal agent, to produce an extracellular xylanase, and to identify isolates based on 16S rRNA gene sequences. Actinomycetes were isolated using Humic-acid Vitamin-B agar (HV) media. Actinomycetes colonies that grow on the medium HV was subsequently purified by growing them on yeast malt agar (YMA) media), then an antagonistic test of selected bacteria against Bacillus sp., Escherichia coli, Fusarium oxysporum, and Sclerotium sp was performed. Xylanase activity test was detected by observing a clear zone, followed by identification. Total of 35 isolates of actinomycetes isolated based on their colony morphology characteristics and diverse types of spore chains showed Streptomyces spp. of isolates CFR-06, CFR-15, CFR-17, CFR-18, and CFR-19 were able to inhibit the growth of Bacillus sp.. The highest inhibition zone has a diameter of 10.1 mm (isolate CFR-17). Isolates CFR-01 and CFR-15 were able to inhibit the growth of E. coli with the highest inhibition zone diameter of 5.1 mm (isolate CFR-15). Isolates CFR-29 and CFR-12 were able to inhibit the growth of F. oxysporum while isolate CFR-35 were able to inhibit the growth of Sclerotium sp.. Xylanase activity test showed that isolates CFR-12, CFR-20, CFR-22, CFR-24, CFR-25, CFR-30, CFR-33, CFR-34 have an ability to produce extracellular xylanase enzyme. Actinomycetes isolate (Xyl_22) as a potential xylanase enzyme producer was closely related with Streptomyces drozdowicii by the maximum similarity of 99%.How to CiteSipriyadi, S., Lestari, Y., Wahyudi, A., Meryandini, A., Suhartono, M. T. (2016). Exploration Potential CIFOR Forest actinomycetes origin as Antimicrobial, Anti Fungus and Producing Enzymes Extracellular Xylanase. Biosaintifika: Journal of Biology Biology Education, 8(1), 94-102.